Teori ma’âlât al-af`âl dalam maqâshid syarȋ`ah dan aplikasinya pada permasalahan fiqih kontemporer - helmi basri; Hidayatullah Ismail (State Institute of Islamic Studies (IAIN) Salatiga, 2019)
This paper is a literature study that seeks to explore the classical literature on the theory of ma'âlât Al-Afâl. This theory is a concept that focuses on efforts to read predictions of what will happen from an action taken, then the prediction will be used as a benchmark in establishing the law between allowed or prohibited. This theory has a high urgency in the contemporary ijtihad fiqih region, because the nature of contemporary jurisprudence itself tends to rely on benefit. It is the benefit prediction that can be used as a legal backing even though the consequences will be to leave the original law contained in the text. Besides mashlahah, there are several factors which require that the concept of ma'âlât Al-Af'âl is recognized in the realm of ijtihad, such as sad Al-Zarîah, Al-Dharûrah, raf`u Al-Haraj and ta`lil Al-Ahkâm. The conclusion obtained is that this predictive theory is really needed in solving contemporary problems, because the benchmark is the maqâshid syarîahah which leads to one word namely